1993
DOI: 10.1159/000261587
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Xylitol Chewing Gum in the Prevention of Dental Caries: A Follow-Up 5 Years after Termination of a Prevention Program

Abstract: About 65% of the original 258 children who participated in 1982–1984 in a caries prevention program involving the use of xylitol chewing gum were retrieved in 1989 for a follow-up study. Ninety-five subjects from the original xylitol (X) group and 70 subjects from the original control (no-gum, C) group were available. In 1984, when the children completed the program at the age of 13-14 years, the caries scores were significantly lower in children who had used xylitol gums daily, compared with the C group. In 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 9 publications
(18 reference statements)
2
43
0
4
Order By: Relevance
“…After two years, this blind study showed a mean reduction in caries in the children chewing xylitol gum of 44% compared with the control group who did not chew any gum. 18 The caries preventive effectiveness was observed three 22 and five years 26 after discontinuation of the use of xylitol -the greatest long-term preventive effect being seen on second permanent molars which erupted during the xylitol gum trial. 39 Scheie and Fejerskov, 12 in their review of this trial, point out that an important factor to be considered in the interpretation of the results was the impact that chewing xylitol gum had on decreasing the intake of conventional solid sweets during the trial and they also suggest that participation in the trial may have raised oral health awareness during the subsequent five years.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 99%
“…After two years, this blind study showed a mean reduction in caries in the children chewing xylitol gum of 44% compared with the control group who did not chew any gum. 18 The caries preventive effectiveness was observed three 22 and five years 26 after discontinuation of the use of xylitol -the greatest long-term preventive effect being seen on second permanent molars which erupted during the xylitol gum trial. 39 Scheie and Fejerskov, 12 in their review of this trial, point out that an important factor to be considered in the interpretation of the results was the impact that chewing xylitol gum had on decreasing the intake of conventional solid sweets during the trial and they also suggest that participation in the trial may have raised oral health awareness during the subsequent five years.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 99%
“…It has been shown that the anticariogenic effect of xylitol lasts for several years after the practice of consuming xylitol daily has been discontinued and is associated partly with the reduction in the total levels of S. mutans and partly with the decrease in the amount and adhesiveness of dental plaque (8). Some studies have failed to document any long-term decrease in the amount of S. mutans bacteria, however (13,19), and this has been explained by the selection of bacterial strains: habitual use of xylitol may select S. mutans strains which are up to 87% nonexpressive of the fructose phosphotransferase enzyme (17) and are thought to have lower adhesiveness to enamel and, therefore, lower virulence (7,12).…”
Section: Fig 2 In Vitro Growth Of S Mitismentioning
confidence: 99%
“…In vivo there was also no reduction of the acidogenic response of dental plaque to sucrose after periods of using xylitol chewing gums [Wennerholm, et al, 1994] or xylitol mouth rinses [Lingström et al, 1997]. It has been proposed that xylitol weakens the caries-inductive properties of dental plaque colonizing newly erupting tooth surfaces [Isokangas et al, 1993] and that such a caries-protective effect might persist several years after the cessation of use of xylitol products [Hujoel et al, 1999]. From animal experiments, it has been concluded that xylitol is anticariogenic [Havenaar et al, 1984].…”
mentioning
confidence: 99%